Assessment of Nepal’s Foreign Policy and Diplomacy towards China and India - Budhathoki, Hemanta (Cognition, 2024)
The present foreign policies of Nepal are based on the Charter of the United Nations, non-alignment, principles of Panchasheel (peaceful co-existence, mutual respect for territorial integrity, sovereignty, and independence; non–aggression; non–interference in each other’s internal affairs and Equality and mutual benefit), international law and the norms of world peace, taking into consideration of the overall interest of the nation while remaining active in safeguarding the sovereignty, territorial integrity, independence, and  national interest. The foreign policy of Nepal has been changing over the years. After unofficial blockade of immediate neighbor India, the challenges and opportunities are seen in the sky of Nepalese foreign policy. The major emerging challenges of Nepalese foreign policy are to balance the foreign policy with India and China continuation of independent foreign policy, recognize and prioritize the national interest, modernization of foreign policy, political consensus, national unity, political consensus, and good leadership, successful conduction of economic diplomacy, etc. Diplomacy is one of the powerful means or instruments of achieving the goals of foreign policy.  The goals of foreign policy are guided by the national interests of concerned states. Diplomats are the actors who plays role according to the foreign policy of the concern state. Diplomats have to perform different functions and discharge different duties with their different roles and capacities. In other words, it is the task for the diplomat to act in different capacities and to play different a role because diplomacy itself is a serious business which requires different capacities and role by the diplomats. The major responsibility of diplomat is the promotion and protection of the national interests of Nepal. Therefore, the proficient diplomat should require making diplomacy effective.